Use of multiple methods to measure impact of a centralized call center on academic health system community pharmacies - Nickman, Nancy A; Drews, Frank A; Tyler, Linda S; Kelly, Michael P; Ragsdale, Russell J; Rim, Matthew (American journal of health-system pharmacy, 2019)
The process and methods used in an impact assessment of a centralized pharmacy call center on community pharmacy employee patient safety climate perceptions, telephone distractions/interruptions, and prescription filling efficiency are described. A broad-based team designed a multi-faceted, pre-post call center implementation analysis that included multiple change assessment measures. First, yearly administration of the Agency for Healthcare Research and Quality Community Pharmacy Survey on Patient Safety Culture was used to assess patient safety climate based on employee perceptions of a safe working environment and potential for errors due to interruptions and distractions. Evaluative measures of staff workload that assessed telephone interference with prescription filling activities pre and 3 months post implementation included (1) the NASA Task Load Index, (2) multi-tasking observations through shadowing of pharmacists and technicians to count number of interruptions/distractions per prescription "touched," and (3) self-reported work sampling to assess proportional time estimates of clinical, professional, and technical activities. Finally, pharmacy efficiency and prescription filling capacity were assessed using operational measures (prescriptions filled, patients served, phone call volume changes, prescription rework counting). Data analysis included summary statistics, Student's t-test, and chi-square analysis, as appropriate, in addition to assessing convergence and agreement among measures. Every evaluative method showed a positive outcome from call center implementation, although individual pharmacies may have accrued greater benefit from call reduction than others. Multiple analysis methods can be used to evaluate the impact of workflow changes.